2005
DOI: 10.1097/01.alc.0000151986.96710.e0
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use Disorders Identification Test (AUDIT): Establishment of Cut-off Scores in a Hospitalized Chinese Population

Abstract: The Chinese version of the AUDIT gave the same cutoff point for harmful alcohol use by Taiwanese individuals as that set by the World Health Organization. This finding shows that this cutoff point is generally appropriate in screening for problem alcohol consumption. Moreover, the cutoff AUDIT score of 11 for alcohol dependence provides a reference for screening in Taiwanese clinics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 6 publications
4
57
2
1
Order By: Relevance
“…Six validation studies published in English on the Chinese version of the AUDIT conducted in Taiwan, Hong Kong (Chen, Chen, & Cheng, 2004Leung & Arthur, 2000;Tsai, Tsai, Chen, & Liu, 2005;Wu et al, 2008), and Tibet (Guo et al, 2008) were identified. Guo et al (2008), adapting the measurement of a standard drink to account for Tibetans' self-brewed alcoholic beverages, found that cutoff values of 10 and 13 were effective for identifying alcohol abuse and AD, respectively, with sensitivity and specificity for both > 0.84.…”
Section: Detection Of Alcohol Use Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Six validation studies published in English on the Chinese version of the AUDIT conducted in Taiwan, Hong Kong (Chen, Chen, & Cheng, 2004Leung & Arthur, 2000;Tsai, Tsai, Chen, & Liu, 2005;Wu et al, 2008), and Tibet (Guo et al, 2008) were identified. Guo et al (2008), adapting the measurement of a standard drink to account for Tibetans' self-brewed alcoholic beverages, found that cutoff values of 10 and 13 were effective for identifying alcohol abuse and AD, respectively, with sensitivity and specificity for both > 0.84.…”
Section: Detection Of Alcohol Use Disordersmentioning
confidence: 99%
“…Guo et al (2008), adapting the measurement of a standard drink to account for Tibetans' self-brewed alcoholic beverages, found that cutoff values of 10 and 13 were effective for identifying alcohol abuse and AD, respectively, with sensitivity and specificity for both > 0.84. Tsai et al (2005) found that a cut score of 11 had the best predictive value for AD (sensitivity, 0.94; specificity, 0.63), while a cut score of 8 (sensitivity, 0.96; specificity, 0.85) is recommended for identifying harmful drinking in a Taiwanese clinic (N = 112). Using the Mandarin Chinese version of the AUDIT, Wu and colleagues (2008) found that a cutoff of 7 was optimal to detect hazardous drinking among hospitalized Chinese patients in Taiwan.…”
Section: Detection Of Alcohol Use Disordersmentioning
confidence: 99%
“…These clinics and wards were chosen because they are where most patients with alcohol or smoking problems are seen in Taiwan [26]. Patients were included if they met these criteria: 1) 20 years old, 2) outpatients/inpatients in the above clinics/wards, 3) have mobile phone or email access, and 4) able to read Chinese.…”
Section: Sample and Settingmentioning
confidence: 99%
“…Within the survey system, we set up four questionnaires/scales: the Chinese-version Fagerstrom Tolerance Questionnaire (C-FTQ) [27], Chinese-version AUDIT (C-AUDIT) [26], Betel Nut Dependency Scale (BNDS) [28], and a sociodemographic form. The C-FTQ was chosen because it has been used as a screening tool for tobacco control by Taiwan's Health Promotion Administration, Ministry of Health and Welfare [27].…”
Section: The Web-based Survey Systemmentioning
confidence: 99%
See 1 more Smart Citation